Pherecydes of Syros: The One Who Didn't Say Everything in a Mythical Way - A. de Azevedo, Cristiane (Revista Archai, 2025)
Aristotle tells us in Metaphysics that Pherecydes did not speak everything in mythological language (1091b8), because, in his dialogue with the mythical tradition, he provides us with a cosmology that is not only marked by action gods. In his narrative about the origin of the cosmos, Pherecydes presents original divine powers generating from elements such as water, air and fire. One of these divine powers, Zás, working with love, and not as a warrior, embroidering a cloak and transforming himself into Eros to be able to acquire the generating power of everything that is. Therefore, Pherecydes reformulates both the narratives regarding divine events and those about the emergence of the cosmos, not depending exclusively on action gods. In this work I intend to explain how Ferécides’ thinking is inserted in the process of development of thought in the face of astonishment of what is.